Against all odds : leadership and The handmaid's tale - Wildermuth, Cris (Exploring effective leadership practices through popular culture, 2024)
The problems we face in the second decade of the twenty-first century are too significant to be solved by a few chosen heroes. Consequently, the role of leadership educators and authors extends beyond encouraging "natural leaders" to accept the leadership call. Instead, our role is to inspire all global citizens to take the baton when needed. Against All Odds explores leadership through the lens of the characters from HULU's TV adaptation of The Handmaid's Tale and the original novel by Margaret Atwood, alongside Atwood's more recent sequel The Testaments (2019), analyzing the ethical dimensions of leadership. In particular, Wildermuth highlights the roles and responsibilities of leaders without authority during times of change and uncertainty. Each chapter of the book uses characters and storylines from the world of The Handmaid's Tale and The Testaments to help the reader connect theories, practices, and consequences of leaders' actions. Against All Odds reinforces the key message that leadership is not the job of a few but the responsibility of all, prompting all leaders to reflect on and improve their own approaches. Exploring Effective Leadership Practices through Popular Culture aims to bring examples, theory and methodology of leadership to life by analyzing academic concepts through popular culture examples that will appeal to a broad range of readers.